Examination of Coliform and Escherichia coli Contamination in Refilled Drinking Water in Cirebon Regency, Indonesia - Shonia, Ana Naela; Fitriani, Hikmah; Indrakusuma, Mohammad Erwin (GHMJ (Global Health Management Journal), 2025)
Background: Refillable drinking water is a commonly used source of water for the public. Contamination of this water can lead to various diseases, including waterborne diarrhea. Coliform bacteria and Escherichia coli are indicators of faecal contamination and can cause waterborne diseases. This study aims to determine whether Coliform and Escherichia coli are present in refillable drinking water in Cirebon Regency. Aims: To identify the presence of Coliform and Escherichia coli bacteria in refillable drinking water in Cirebon Regency. Methods: This descriptive study employed purposive sampling to collect six samples of refillable drinking water from six different depots located in Cirebon Regency. Each sample was tested four times using various laboratory tests, including Nutrient Agar, Mac Conkey Agar, Gram Staining, IMVIC, and TSIA. Results: All samples showed the presence of Coliform (100%), as shown by the Mac Conkey Agar test indicating lactose fermentation and Gramme Staining revealing rod-shaped bacteria. However, Escherichia coli was not found (0%) in any of the samples. The results of the Mac Conkey Agar test as a lactose fermenter, Gram Staining showing rod-shaped bacteria, and IMVIC tests showed the following profile: Indole +, MR +, VP -, Citrate -, and TSIA: A/A, H₂S -, Gas +. While Escherichia coli was absent, the detection of other Coliforms suggests persistent hygiene issues; Citrobacter freundii and Klebsiella were found to be Coliform bacteria. Conclusion: No Escherichia coli were detected in any of the samples, but Coliform bacteria were found in 6 out of 6 samples (100%). The maintenance of refillable drinking water depots is crucial for public health. Owners must frequently clean and disinfect the reservoirs to prevent contamination. Additionally, authorities are responsible for regularly monitoring the hygiene and sanitation of these depots.